Children's Environmental Waste Reduction Education Rawa Simprug IX, South Jakarta, Special Capital Region of Jakarta to Increase Public Awareness of Environmental Issues - Wira Aulia; Ari Rahman; Teuku Mahlil; Evi Siti Sofiyah; Ariyanti Sarwono; I Wayan Koko Suryawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
ABSTRACT Education is something that serves as a foundation for humans. As educational activists, we can raise a better generation by conducting teaching activities for the nation's children to hone their academic and non-academic abilities outside formal schools. The large number of students dropping out of school causes non-formal education to have an important role in fostering environmental awareness. This activity aims to foster a sense of concern for environmental knowledge, especially among children in Rawa Simprug IX, South Jakarta, Special Capital Region of (DKI) Jakarta. In addition, it also aims to enhance children's interest in reading from an early age and their understanding of various lessons that have been or have not been obtained in formal schools. This activity was conducted from August 2019 to November 2019. The peak of the event was held on Sunday, November 24, 2019. In this activity, several books could be loaned to children for on-the-spot reading (in the Madani Rubric). The book was carried by a mobile library car from the South Jakarta Administration City Library and Archives Service. There were approximately 30 children of Rawa Simprug IX who took part as the participants in this event. This activity teaches children in the Rawa Simprug IX area who need additional education with the help of HMTL (Himpunan Mahasiswa Teknik Lingkungan) and some lecturers from Pertamina University as the teaching staff. The children were also taught about the environment, particularly reducing plastic waste by using drinking bottles. The achievement of this activity is a recycling product made by the target community themselves.